2010
DOI: 10.1016/j.rmed.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Mass of intercostal muscles associates with risk of multiple exacerbations in COPD

Abstract: This study shows that the risk for multiple admissions due to a COPD exacerbation associates with a marked decrease in the CSA of the intercostal muscle compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 43 publications
2
42
0
1
Order By: Relevance
“…Our findings dovetail with previous well-established reports that quantitative assessments of both the intercostal muscles and quadriceps are associated with exacerbations and mortality in COPD (11,12). The uniqueness of our study lies in the ease and practicality of obtaining additional clinically relevant information pertaining to skeletal muscle size from readily available CT scans of the chest.…”
Section: Original Researchsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings dovetail with previous well-established reports that quantitative assessments of both the intercostal muscles and quadriceps are associated with exacerbations and mortality in COPD (11,12). The uniqueness of our study lies in the ease and practicality of obtaining additional clinically relevant information pertaining to skeletal muscle size from readily available CT scans of the chest.…”
Section: Original Researchsupporting
confidence: 86%
“…Although many of these investigations have focused on the airway and parenchymal manifestations of this process, use of the additional imaging data available external to the lungs to assess muscle wasting has been more limited. Güerri and colleagues reported that smaller cross-sectional area of the intercostal and abdominal muscles was associated with a history of more frequent acute exacerbations of COPD (AECOPD) (11). In a larger cohort, Marquis and colleagues demonstrated that mid-thigh cross-sectional area was independently predictive of death in 142 smokers (12).…”
mentioning
confidence: 99%
“…In fact, patients with history of multiple hospital admissions for COPD exacerbation have greater expiratory muscle strength than more stable patients. 7,8 Regarding quadriceps peak torque, we observed no difference between the 3 assessment days, similar to Troosters et al 18 Two other studies, 5,6 however, found a decrease of 5% of predicted in quadriceps peak torque during the hospitalization period. Besides the study of Troosters et al, 18 which found no decrease in this variable, Spruit et al 6 found that 48% of their subjects had no change or an increase in quadriceps peak torque.…”
Section: Discussionsupporting
confidence: 88%
“…Two recent cross-sectional studies found that respiratory muscle dysfunction is associated with an increased risk of hospital admission for exacerbation. 7,8 Two other prospective studies identified inspiratory muscle overload as a risk factor for hospitalization for exacerbation. 9,10 Surprisingly, the respiratory muscle function during and after COPD exacerbation seems to have been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In COPD, CT imaging of muscle groups, including intercostal muscles and mid-thigh area, has been used to assess low muscle mass and to predict adverse clinical outcomes[14, 15]. In patients with cancer, axial CT from the third lumbar vertebra (L3) region of the spine has been used to calculate FFMI[1618].…”
Section: Introductionmentioning
confidence: 99%